ANALISIS PENERAPAN CASH BASIS DAN ACCRUAL BASIS SERTA DAMPAKNYA TERHADAP PENYAJIAN LAPORAN KEUANGAN PADA PERUSAHAAN XYZ - Andri, Hendri Kartika (STIE PEMBANGUNAN TANJUNGPINANG, 2024)
This research aims to analyze the implementation of cash basis and accrual basis accounting methods at XYZ Company and examine their impact on the quality of the company's financial statement presentation. The selection of appropriate accounting methods becomes a crucial factor in providing accurate and relevant financial information for stakeholders. This study employs a qualitative approach with data collection techniques through direct observation, in-depth interviews, and documentation studies. Research informants were selected purposively, consisting of the head of finance division, internal auditor, operational manager, and finance director who possess deep understanding of the company's accounting recording system. This study found that when companies experience development and growth, the use of accrual basis method becomes more relevant as it provides a more accurate and timely overview of the company's financial position compared to cash basis. Although cash basis usage can be considered in the early stages of business establishment due to its simplicity, companies need to prepare for the transition to accrual basis for the future. This aligns with the provisions of Financial Accounting Standards (SAK) which require the use of accrual basis in the presentation and disclosure of financial statements that reflect the actual financial condition. This research provides practical contributions for company management in determining optimal accounting recording strategies according to business development stages and compliance with applicable accounting standards